From Shariâa âAyniyya to Shariâa Hududiyya: Shahrourâs Interpretation on Quranic Legal Verses - Khusen, Moh (Al-Jamiah: Journal of Islamic Studies, 2012)
This article elaborates a new paradigm in the interpretation of Qurâanic legal verses conducted by a Syrian thinker, Mohammad Shahrour. This study shows that, according to Shahrour, Islamic jurisprudence is not ââayniyyaâ, but âhââududiyyaâ since for him, all legal rules carried by the verses represent the limits of Allah which people can behave. Shariâa hâududiyya proves that Shahrourâs approach to the Quranic legal verses can be characterized as an open-ended process of socio-political and moral codes. Still holding on to the tool of textual analysis but combining it with a new perspective, hâududiyya, Shahrour manages to be faithful to the text and at the same time, compatible with the ideas and values of modernity and humanism. Elaborated by other theories from other disciplines, especially mathematics and physics, Shahrour provides six types of limits which encapsulate all Shariâa cases equipped with their characteristics, differentiations and implementations. [Artikel ini menjelaskan paradigma baru dalam menafsirkan ayat-ayat hukum dalam al-Quran seperti diperkenalkan oleh seorang pemikir berkebangsaan Syria, Mohammad Shahrour. Artikel ini memperlihatkan bahwa, menurut Shahrour, ayat-ayat hukum dalam al-Quran itu tidak bersifat ââayniyyaâ, namun âhâududiyyaâ karena berfungsi untuk membatasi. Shariâa hâududiyya yang diperkenalkan Shahrour menjelaskan bahwa pendekatan terhadap ayat-ayat hukum dalam al-QuranÂ  bersifat terbuka. Dengan tetap berpijak pada pendekatan tekstual terhadap al-Quran sembari memperhatikan pandangan baru, hâududiyya, Shahrour berhasil mempertemukan teks al-Quran dengan ide-ide dan norma-norma modernitas dan humanisme. Dijelaskan melalui teori-teori yang berkembang di disiplin ilmu lain, utamanya matematika dan fisika, Shahrour memperkenalkan enam tipe batasan Shariâa.]